PEMANFAATAN WORTEL (Daucus Carota L.) DALAM PEMBUATAN ES KRIM DENGAN PENAMBAHAN JERUK KASTURI (Citrus Microcarpa B.) - CHODIJAH CHODIJAH; NETTI HERAWATI; AKHYAR ALI (Universitas Riau, 2019)
Ice cream is a type of semi-solid food made by freezing ice cream flour from sugar, a mixture of milk, animal orvegetable fat, with or without other food additives permitted. The purpose of this study was to determine theeffect of the addition of carrot (Daucus carota L.) and kasturi orange (Citrus microcarpa B.) in making icecream on the quality and sensory properties of ice cream in accordance with the Indonesian National Standard(01-3713-1995). The experiment was conducted experimentally using a completely randomized design (RAL)with 4 treatments and 4 replications to obtain 16 experimental units. The treatment used in the study was W1(ratio of carrot extract : kasturi orange 80:20), W2 (ratio of carrot extract : kasturi orange 70:30), W3 (ratio of carrotextract : kasturi orange 60: 40) and W4 (ratio of carrot extract : kasturi orange juice 50:50). The data obtained wereanalyzed statistically using analysis of variance (ANOVA). If F calculation was equal with or more than F table,the further testing is done by duncan’s new multiple range test (DNMRT) at 5% level. The best formulation ofice cream was using W2 treatment (ratio of carrot extract 70% and kasturi orange 30%). The resulting ice creamtotal sugar of 60,16%, total solids of 66.11%, fat of 5.01%, protein of 3.08, overrun of 20.41%, melting time of8.07%, and sensory assessment. Over all sensory assessment was favored by panelist with descriptions ofyellow, scented with citrus oranges and carrots, sour taste to unctuous and soft in texture.